Ефективна маса атома 4He в надплиннiй i нормальнiй фазах - Vakarchuk, I. O.; Hryhorchak, O. I.; Pastukhov, V. S.; Prytula, R. O. (Publishing house "Academperiodika", 2019)
The formula for the temperature dependence of the effective mass of a 4He atom in the superfluid and normal phases is obtained. This expression for the effective mass allows one to eliminate infra-red divergences, being applicable at all temperatures, except for a narrow fluctuation region 0.97 ≤ T/Tc ≤ 1. In the high and low temperature limits, as well as in the interactionless limit, the obtained expression reproduces the well known results. The temperature dependence of the heat capacity and the phase transition temperature Tc ≈ 2.18 K are calculated, by using the formula obtained for the effective mass. In the framework of the approach proposed in this work, the small critical index n is determined in the random phase approximation. The obtained value corresponds to the well known result.